2019
DOI: 10.1103/physrevb.99.184506
|View full text |Cite
|
Sign up to set email alerts
|

Single-orbital realization of high-temperature s± superconductivity in the square-octagon lattice

Abstract: We propose possible high-temperature superconductivity (SC) with singlet s ± -wave pairing symmetry in the single-orbital Hubbard model on the square-octagon lattice with only nearest-neighbor hopping terms. Three different approaches are engaged to treat with the interacting model for different coupling strengths, which yield consistent result for the s ± pairing symmetry. We propose octagraphene, i.e., a monolayer of carbon atoms arranged into this lattice, as a possible material realization of this model. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…Octagon-structure materials can be expected to be a good candidate for hydrogen storage. It is a possible high-temperature superconductor [ 24 ]. In 2015, Lu et al fabricated free-standing octagon-shaped carbon nanofiber [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Octagon-structure materials can be expected to be a good candidate for hydrogen storage. It is a possible high-temperature superconductor [ 24 ]. In 2015, Lu et al fabricated free-standing octagon-shaped carbon nanofiber [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The square-octagon lattice has been attracting much attention lately due to the plethora of novel phases predicted to occur in the system. They range from a quantum magnetic phase under the competition between temperature and on-site repulsive interaction [41], to topological insulating phases induced by spin-orbit coupling or non-Abelian gauge fields [42][43][44], and even high-temperature superconductivity with singlet s ± -wave paring symmetry [45]. Moreover, it has been shown that trivial and nontrivial flat bands can be tuned on the square octagon lattice by considering the addition of next-nearest neighbour hopping and an external magnetic flux [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…It is a possible high‐temperature superconductor. [ 15 ] Recently, Zhong's research group fabricated graphene‐like nanoribbons, which periodically embedded with four‐ and eight‐membered rings. [ 16 ] The Raman spectra can help people to determine the grown 2‐D materials.…”
Section: Introductionmentioning
confidence: 99%